Foodborne botulism associated with home-preserved turnip tops in Italy - Fabrizio Anniballi; Elisa Chironna; Sara Astegiano; Alfonsina Fiore; Bruna Auricchio; Giuseppina Buonincontro; Maria Corvonato; Vincenzo Segala; Giuseppina Mandarino; Dario De Medici; Lucia Decastelli (Istituto Superiore di Sanità, 2015)
In Italy, foodborne botulism is a rare disease mainly due to home-preserved food. In the case reported here, clinical diagnosis was performed on the basis of clinical signs and referred consumption of home-preserved turnip tops in oil. Definitive diagnosis was performed by detection of botulinum toxin in sera and neuro-toxigenic organisms in stools and leftover food. This case report highlights the need of a high medical awareness, prompt clinical diagnosis, and synergic collaboration among the health authorities for a correct management of botulism as well as disease containment.